2010
DOI: 10.1002/mrc.2653
|View full text |Cite
|
Sign up to set email alerts
|

The effects of anticalcification treatments and hydration on the molecular dynamics of bovine pericardium collagen as revealed by 13C solid‐state NMR

Abstract: This article describes a solid-state NMR (SSNMR) investigation of the influence of hydration and chemical cross-linking on the molecular dynamics of the constituents of the bovine pericardium (BP) tissues and its relation to the mechanical properties of the tissue. Samples of natural phenethylamine-diepoxide (DE)- and glutaraldehyde (GL)-fixed BP were investigated by (13)C cross-polarization SSNMR to probe the dynamics of the collagen, and the results were correlated to the mechanical properties of the tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…In agreement with this aspect, the molecular dynamics of the ECM are also related to the elastic properties of bone. Thus, the application of NMR techniques for the characterization of de novo generated tissues in implants as well as the function of the related tissues is promising .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this aspect, the molecular dynamics of the ECM are also related to the elastic properties of bone. Thus, the application of NMR techniques for the characterization of de novo generated tissues in implants as well as the function of the related tissues is promising .…”
Section: Discussionmentioning
confidence: 99%
“…These analyses showed that is crucial to establish a compromise between the RF power and the MAS frequency in order to avoid intensity losses in the amplitude of the DIPSHIFT rotor echo at t 1 ¼ Nt r that are unrelated to molecular motion. This kind of imperfection has been observed in DIPSHIFT results in the literature [17][18][19][20][21][22], but neither a clear explanation nor ways to avoid it were discussed as yet. Using Average-Hamiltonian Theory, AHT [23], we identified the origin of the artifacts and established the conditions to avoid them.…”
Section: Introductionmentioning
confidence: 87%
“…Therefore, it is crucial to know how the spin system behaves in an as-realistic-as-possible situation and to predict how such unwanted effects challenge the acquired signal, in order to avoid experimental artifacts that lead to misinterpretations. By means of the spin dynamics simulations, we found that under certain conditions involving the MAS frequency, the number of recoupling periods, and the RF decoupling frequency, the initial magnetization is not fully recovered for the acquired rotor echo, which in fact explains many of the experimental imperfections reported for DIPSHIFT experiments [17][18][19][20][21][22]. Thus, the aim of this section is to present and discuss these features first by means of simulations.…”
Section: Artifacts and Correction Procedures In Dipshift Variantsmentioning
confidence: 95%
“…Next, MAS applications on collagen without the need for isotopic labeling were conducted 69 , 80 - 82 . These studies reported the assignments of the collagen spectra as well as information on the hydration behavior of collagen and more importantly, provided the prerequisites for the solid-state NMR analysis of intact biological tissues.…”
Section: Methods Of In Vitro Ecm Characterizationmentioning
confidence: 99%